Heat transfer behaviour of a dilute impinging air-water mist jet - Quinn, Cian (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2015)
While the convective heat transfer characteristics of conventional air jets have received a large amount of attention, mist Jets remain relatively under-represented within the literature. The mist jet has the potential to offer significant heat transfer enhancement using very small amounts of liquid. However, the mechanisms by which this is accomplished are not fully understood. Thus, an in-depth investigation into the heat transfer phenomena of the dilute mist jet is required.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin.